Encouraging reading through ICTs: an analysis of the Monica's gang video - Coqueiro, Naiara Porto da Silva (2023)
This work presents a discussion on the theme of Information and Communication Technologies - ICTs as a support capable of influencing children and adolescents, encouraging a taste for reading literary texts. In this analysis, when discussing possible uses of these tools to encourage reading, a video from Turma da Mônica (Maurício de Sousa), available on YouTube, was analyzed. The theoretical basis is based uses a bibliographical on the subject and from the perspective of video taxonomy to analyze the video. So, the results demonstrate that the use of ICTs can arouse interest in reading, expanding the possibilities of training readers.